Annual Acoustic Presence of Fin Whale (Balaenoptera physalus) Offshore Eastern Sicily, Central Mediterranean Sea - Sciacca, V.; Caruso, F.; Beranzoli, L.; Chierici, F.; De Domenico, E.; Embriaco, D.; Favali, P.; Giovanetti, G.; Larosa, Giuseppina; Marinaro, G.; Papale, E.; Pavan, G.; et al. (PLOS ONE, 2015)
In recent years, an increasing number of surveys have definitively confirmed the seasonal presence of fin whales (Balaenoptera physalus) in highly productive regions of the Mediterranean Sea. Despite this, very little is yet known about the routes that the species seasonally follows within the Mediterranean basin and, particularly, in the Ionian area. The present study assesses for the first time fin whale acoustic presence offshore Eastern Sicily (Ionian Sea), throughout the processing of about 10 months of continuous acoustic monitoring. The recording of fin whale vocalizations was made possible by the cabled deep-sea multidisciplinary observatory, “NEMO-SN1”, deployed 25 km off the Catania harbor at a depth of about 2,100 meters. NEMO-SN1 is an operational node of the European Multidisciplinary Seafloor and water-column Observatory (EMSO) Research Infrastructure. The observatory was equipped with a low-frequency hydrophone (bandwidth: 0.05 Hz–1 kHz, sampling rate: 2 kHz) which continuously acquired data from July 2012 to May 2013. About 7,200 hours of acoustic data were analyzed by means of spectrogram display. Calls with the typical structure and patterns associated to the Mediterranean fin whale population were identified and monitored in the area for the first time. Furthermore, a background noise analysis within the fin whale communication frequency band (17.9–22.5 Hz) was conducted to investigate possible detection-masking effects. The study confirms the hypothesis that fin whales are present in the Ionian Sea throughout all seasons, with peaks in call detection rate during spring and summer months. The analysis also demonstrates that calls were more frequently detected in low background noise conditions. Further analysis will be performed to understand whether observed levels of noise limit the acoustic detection of the fin whales vocalizations, or whether the animals vocalize less in the presence of high background noise. Published e0141838 3A. Ambiente Marino JCR Journal open